Green Chemistry and Chemical Engineering - Han, Buxing; Wu, Tianbin (Encyclopedia of Sustainability Science and Technology Series, 2019)
This expanded, revised, and updated second edition of Innovations in Green Chemistry and Green Engineering provides a comprehensive introduction to the state-of-the-art in this key area of sustainability research. Processes that meet the objectives of green chemistry and chemical engineering minimize waste and energy use, and eliminate toxic by-products. Given the ubiquitous nature of products from chemical processes in our lives, green chemistry and chemical engineering are vital components of any sustainable future. Peer-reviewed articles from worldwide experts present the latest developments on topics ranging from organic batteries and green catalytic transformations to green nanoscience and nanotoxicology. Now under the leadership of distinguished Editors from the Chinese Academy of Sciences, this volume in the Encyclopedia of Sustainability Science and Technology, Second Edition, is an essential, one-stop reference for professionals in researchand industry. The book also fills the need for an authoritative course text in environmental and green chemistry and chemical engineering at the upper-division undergraduate and graduate levels.